Constitutive heterochromatin and nucleolus organizer region in the knifefish, Apteronotus albifrons (Pisces, Apteronotidae) - Toledo, Lurdes F. de Almeida [UNESP]; Foresti, F. [UNESP]; Toledo, S. de Almeida [UNESP] (Birkhauser Verlag Ag, 1981)
The C-banding and silver staining of the chromosomes of the knifefish Apteronotus albifrons (2n=24), demonstrated the presence of constitutive heterochromatin in the centromeric region of every chromosome, except pair 4, where the entire long arm was darkly stained, the silver stain positive nucleolus organizer region (NOR) being embedded in it. © 1981 Birkhüuser Verlag.